2021
DOI: 10.47672/ajfsn.739
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Starches from Four Local Varieties of Millet in Nigeria.

Abstract: Purpose: The study was carried out to evaluate the physico-chemical properties of starches from four local varieties of millet in salad cream production. Methodology: Starches were extracted from four varieties of millet, two varieties of pearl millet were used namely Gero and Maiwa (Pennisetum glaucum), Tamba-Finger millet (Eluesine coracona) and Acha-Fonio millet (Digitaria exillis) using dry and wet milling processes for characterization and salad cream production. Standard analytical methods were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In RVA, optimum starch gelatinization is represented by the PV of the paste. The value of PV also gives an indication of the ability of the products to swell freely prior to physical breakdown and the binding capacity of starch to form a product (Abah et al, 2020; Eke‐Ejiofor & Oparaodu, 2019). Breakdown (BD) viscosity which is the measure of the proneness of cooked starch granule to disintegration is majorly influenced by content and chain length distribution of amylose fractions in the starch.…”
Section: Nutritional and Antioxidant Profilementioning
confidence: 99%
“…In RVA, optimum starch gelatinization is represented by the PV of the paste. The value of PV also gives an indication of the ability of the products to swell freely prior to physical breakdown and the binding capacity of starch to form a product (Abah et al, 2020; Eke‐Ejiofor & Oparaodu, 2019). Breakdown (BD) viscosity which is the measure of the proneness of cooked starch granule to disintegration is majorly influenced by content and chain length distribution of amylose fractions in the starch.…”
Section: Nutritional and Antioxidant Profilementioning
confidence: 99%
“…Millets are used in soups, stews or as a cooked cereal, and also are popped, roasted or sprouted and used. Millets contain an average of 10-12% protein (Eke-Ejiofor et al, 2021), which is also superior to that of common cereals in terms of their essential amino acid profile.…”
Section: Introductionmentioning
confidence: 99%
“…Millets are used in soups, stews or as a cooked cereal, and also are popped, roasted or sprouted and used. Millets contain an average of 10–12% protein (Eke‐Ejiofor et al, 2021), which is also superior to that of common cereals in terms of their essential amino acid profile. The nutritive value of millets is comparable or even better than the common staples (Gopalan et al, 2004), and they contain almost half the amount of lysine found in quality proteins such as meat.…”
Section: Introductionmentioning
confidence: 99%